The relationship between biomarkers of fungal allergy and lung damage in asthma. Issue 1 (2nd December 2016) - Woolnough, K. F.; Richardson, M.; Newby, C.; Craner, M.; Bourne, M.; Monteiro, W.; Siddiqui, S.; Bradding, P.; Pashley, C. H.; Wardlaw, A. J.
Summary: Background: Immunological biomarkers are the key to the diagnosis of allergic bronchopulmonary aspergillosis (ABPA) and fungal sensitisation, but how these relate to clinically relevant outcomes is unclear. Objectives: To assess how fungal immunological biomarkers are related to fixed airflow obstruction and radiological abnormalities in moderate to severe asthma. Methods: Cross‐sectional study of 431 asthmatics. Inflammatory biomarkers, lung function and an IgE fungal panel to colonising filamentous fungi, yeasts and fungal aeroallergens were measured. CT scans were scored for the presence of radiological abnormalities. Factor analysis informed the variables used in a k‐means cluster analysis. Fixed airflow obstruction and radiological abnormalities were then mapped to these immunological variables in the cluster analysis. Results: 329 (76.3%) subjects were sensitised to ≥ 1 fungi. Sensitisation to Aspergillus fumigatus and/or Penicillium chrysogenum was associated with a lower post‐bronchodilator FEV1 compared with those not sensitised to fungi ((73.0 (95% CI 70.2–76) vs. 82.8 (95% CI 78.5–87.2)% predicted, P < 0.001), independent of atopic status ( P = 0.005)), and an increased frequency of bronchiectasis (54.5%, P < 0.001), tree‐in‐bud (18.7%, P < 0.001) and collapse/consolidation (37.5%, P = 0.002). Cluster analysis identified three clusters: (i) hypereosinophilic ( n = 71, 16.5%), (ii) high immunological biomarker load and high frequency of radiological abnormalities ( n = 34, 7.9%) and (iii) low levels of fungal immunological biomarkers ( n = 326, 75.6%). Conclusions and Clinical Relevance: IgE sensitisation to thermotolerant filamentous fungi, in particular A. fumigatus but not total IgE, is associated with fixed airflow obstruction and a number of radiological abnormalities in moderate to severe asthma. All patients with IgE sensitisation to A. fumigatus are at risk of lung damage irrespective of whether they meet the criteria for ABPA.